Renal Oncocytoma With Both Lymphovascular Invasion and Prominent Intracytoplasmic Vacuole-Like Spaces: A Case Report and Review of the Literature. (May 2022) - Luo, Xunda; Preciado, Christopher; Nayak, Anupma; Schwartz, Lauren E.; Guzzo, Thomas J.; Williamson, Sean R.; Palmer, Matthew B.; Lal, Priti
Here we report a case of renal oncocytoma in a 68 year-old male. The diagnosis was initially made on a needle biopsy 6 years prior to the partial nephrectomy. The case is unique that in addition to the gross and microscopic features commonly seen in renal oncocytomas, both lymphovascular invasion and prominent intracytoplasmic vacuole-like spaces are also present in this tumor. Although vascular invasion is increasingly recognized as compatible with renal oncocytoma, intracytoplasmic vacuoles are a rare and unusual finding that may lead to diagnostic difficulty. The diagnosis of renal oncocytoma was confirmed after immunohistochemistry was performed to argue against succinate dehydrogenase deficient renal cell carcinoma (RCC) and chromophobe RCC. This case highlights the importance for practicing pathologists to recognize the rare co-occurrence of lymphovascular invasion and large intracytoplasmic vacuole-like spaces in renal oncocytoma. Other differential diagnoses may include emerging renal tumor entities, such as the recently-proposed eosinophilic vacuolated tumor.